Efficacy of C-Reactive Protein and WBC Count In Fascial Space Infections of Odontogenic Origin - Deepak Yadav; Sunil Kumar Singh; Ravish Mishra; Laxmi Kandel; Shahid Ali (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Maxillofacial infection is one of the life-threatening conditions. The signs and symptoms alone, may not always be sufﬁcient to judge the severity of infectious process. white blood cells (WBC) counts and C-reactive protein (CRP) levels help to monitor infections in terms of severity, clinical features and duration of hospital stay. So, the present study was aimed to compare the efﬁcacy of CRP level and WBC count in fascial space infections of odontogenic origin. MATERIAL AND METHODS A total of 31 patients of fascial space infection of odontogenic origin aged 11 to 64 years were included in the study. Clinical details were recorded after thorough clinical examination. Venous blood samples from patients were collected on pre-operative day (Day 0), 2nd post-operative day (Day 2) and 5th post-operative day (Day 5) to measure CRP level and WBC counts. RESULTS Out of 31 patients, 20 (64. 51%) patients had high WBC counts whereas all patients had high CRP levels on Day 0. On day 2 and day 5 when compare to day 0, WBC and CRP level decreased signiﬁcantly. On Day 5 alone when compared to Day 2, CRP level decreased signiﬁcantly (p<0.001) and had positive correlation with duration of hospital stay (r = 0.51, p = 0.003). CONCLUSION CRP levels had a high sensitivity for diagnosis of odontogenic fascial space infection. It showed a more consistent correlation with the clinical features and signiﬁcant positive correlation with duration of hospital stay. Thus, CRP should be assessed to monitor fascial space infections as routine practice.